CSF-1 controls cerebellar microglia and is required for motor function and social interaction - Kana, Veronika; Desland, Fiona A; Casanova-Acebes, Maria; Ayata, Pinar; Badimon, Ana; Nabel, Elisa; Yamamuro, Kazuhiko; Sneeboer, Marjolein; Tan, I-Li; Flanigan, Meghan E; Rose, Samuel A; Chang, Christie; et al. (The Journal of experimental medicine, 2019)
Microglia, the brain resident macrophages, critically shape forebrain neuronal circuits. However, their precise function in the cerebellum is unknown. Here we show that human and mouse cerebellar microglia express a unique molecular program distinct from forebrain microglia. Cerebellar microglial identity was driven by the CSF-1R ligand CSF-1, independently of the alternate CSF-1R ligand, IL-34. Accordingly, CSF-1 depletion from Nestin cells led to severe depletion and transcriptional alterations of cerebellar microglia, while microglia in the forebrain remained intact. Strikingly, CSF-1 deficiency and alteration of cerebellar microglia were associated with reduced Purkinje cells, altered neuronal function, and defects in motor learning and social novelty interactions. These findings reveal a novel CSF-1-CSF-1R signaling-mediated mechanism that contributes to motor function and social behavior.